Organizational-Level Characteristics in Right-Wing Extremist Groups in the United States Over Time. (June 2020) - Asal, Victor; Chermak, Steven M.; Fitzgerald, Sarah; Freilich, Joshua D.
This study compares the organizational-level variables of violent and nonviolent far-right extremist groups. This study makes an important contribution by coding for attributes for each specific year that an organization existed. Prior research has only examined organizational characteristics at a single point of time. Our strategy here better specifies differences between violent and nonviolent extremist groups. We used a pooled cross-sectional time series analysis using logistic regression because our dependent variable is dichotomous (the organization used violence this year vs. it did not). We clustered on the organization and we included dummy years to control for time series effects. We also included a lagged variable if the organization used violence in the year before. We found that organizations were more likely to use violence if they were previously involved in violence, had multiple alliances with other extremist groups, had a large membership, had weak or decentralized leadership or a strong ruling council, and advocated for inherent racial or ethnic superiority. These results have important implications for law enforcement and future research on extremism and violence.